Enhancing Supply Chain Visibility in Large Enterprises: A Literature Review - Peesapati, Sri Rama Yashaswi (ExcelingTech, 2024)
Supply Chain Visibility has become an increasingly crucial aspect for large enterprises in today's global and interconnected business landscape. Achieving comprehensive visibility across multiple layers of the supply chain can significantly impact operational efficiency, cost optimization, customer satisfaction and trust. However, attaining supply chain visibility presents various challenges including fragmented data systems, interoperability issues, diverse supplier networks, data quality concerns, and geographical dispersion. Emerging technologies have a great potential to play key role in solving these challenges and facilitating improved supply chain visibility for enterprises. This study aims to provide insights that can inform and guide enterprises to effectively leverage the power of emerging technologies to gain better visibility into their supply chain operations. This paper is based on a comprehensive examination of 30 literary works to provide a thorough analysis of the subject matter. By synthesizing extant research, and practical case studies of large enterprises, the review has uncovered critical insights into the implications of supply chains visibility for both theory and practice in the field of supply chain management, particularly emphasizing the role of technology solutions and case studies. In addition, the integration of case studies provides concrete examples of how leading enterprises are leveraging technology to overcome visibility challenges and achieve operational excellence.